Evaluation of molecular and morphological diversity of the rangeland species of Atriplex canescens (Amaranthaceae) in Iran - Tahmasebi, Abolfazl; Nasrollahi, Fatemeh; Esmaeili, Majid Mohammad (Acta Biologica Szegediensis, 2023)
Atriplex canescens is a polymorphic species that can be deciduous or evergreen depending on the climate. Having an extensive root system, it controls soil erosion very well and is resistant to drought. The present study examined the morphological and genetic diversity of 13 Iranian populations. Multivariate statistical analyses were performed on 25 morphological characteristics (quantitative and qualitative). To assess genetic diversity, eight primers were applied, resulting in 42 bands. With the ANOVA test, all quantitative morphological characteristics among the studied populations were significantly different. Similarly, the AMOVA test revealed that the genetic content of the studied populations was different. Genetic distance and geographic distance were significantly correlated in Mantel's test. Based on morphological studies and the effects of environmental factors (latitude, longitude, and altitude) on genetic structure, different genetic branches have been proposed for A. canescens.